ISOLASI DAN IDENTIFIKASI SENYAWA ISOFLAVON DARI KACANG KEDELAI (Glycine max) - Astiti Asih, I. A. R. (Jurnal Kimia (Journal of Chemistry), 2012)
Isolation and identification of flavonoid compound from soy bean (Glycine max) have been conducted in this research. Extraction of 1740.83 g of soy bean powder with methanol yielded 17.82 g yellowish brown of crude methanol extract. The crude extract was then hydrolysed with 2N HCl. Following partition of hydrolysed product with n-hexane gave 2.61g of n-hexane extract. Phytochemical testing of n-hexane extract gave positive result for flavonoid compound. The n-hexane extract was then subjected to column chromatography for purification. Identification of fraction which contained flavonoid using UV-Vis showed two band peaks at 312.9 nm dan 268.2 nm. Further identification using chemical shift including sodium hydroxide, sodium acetate, sodium acetate:borate acid, aluminium chloride, aluminium chloride-concentrated chloride acid suggested that the compound isolated was isoflavone without any free hydroxyl group and ortho dihydroxy group at ring A. Thr infra red spectra of isolate indicated the presence of characteristic functional group such as aromatic CH, aliphatic C-H, C=O, aromatic C=C, and C-O
Keywords: soy bean (Glycine max), isoflavone